1997
DOI: 10.1152/ajpcell.1997.272.2.c565
|View full text |Cite
|
Sign up to set email alerts
|

Myonuclear accretion is a major determinant of avian skeletal muscle growth

Abstract: The role of satellite cells and DNA unit size in determining skeletal muscle growth was studied after mitotic activity was inhibited in the left pectoralis thoracicus of 2-wk-old tom turkeys by means of a 25-Gy dose of irradiation. Toms were killed and muscle weights were obtained 1 (n = 5), 4 (n = 6), 7 (n = 6), and 15 (n = 4) wk after irradiation. Satellite cell mitotic activity and DNA unit size were determined using enzymatically isolated myofiber segments and image analysis. Irradiated and nonirradiated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 24 publications
2
50
0
1
Order By: Relevance
“…Whereas increases in muscle mass can be misleading because of the possibility of muscle or fiber swelling, we contend that protein content increase is a reliable marker of muscle hypertrophy. In support of our findings, normal muscle growth in young Tom turkeys and young rats occurs when satellite cell proliferation is attenuated (Mozdziak et al 1997;Rosenblatt and Parry 1993). Our results show that muscle hypertrophy can proceed, at least acutely or to a certain extent, without satellite cell proliferation.…”
Section: Discussionsupporting
confidence: 90%
“…Whereas increases in muscle mass can be misleading because of the possibility of muscle or fiber swelling, we contend that protein content increase is a reliable marker of muscle hypertrophy. In support of our findings, normal muscle growth in young Tom turkeys and young rats occurs when satellite cell proliferation is attenuated (Mozdziak et al 1997;Rosenblatt and Parry 1993). Our results show that muscle hypertrophy can proceed, at least acutely or to a certain extent, without satellite cell proliferation.…”
Section: Discussionsupporting
confidence: 90%
“…The primary effect of unweighting is on myotubes/myo®bers, and satellite cell mitotic activity is modulated through a myo®ber pathway. The idea that myo®bers direct satellite cell activity does not contradict the results of Rosenblatt and Parry (1993) or Mozdziak et al (1997) who demonstrated through muscle irradiation that satellite cells are essential for muscle growth because irradiation simply depletes the satellite cell population making them unable to meet the demands of the growing myo®bers. Thus, the current results suggest that the growth rate and/or growth potential of myo®bers are not actively determined by satellite cells even though they are the source of new DNA for growing myo®bers.…”
Section: Discussionmentioning
confidence: 96%
“…In newly hatched chicks, satellite cells proliferate, differentiate and fuse with the adjacent myofibers, which increase myofiber DNA contents and ultimately result in the increase in protein synthesis and muscle fiber hypertrophy (Allen and Goll, 2003). In poultry, SCMA is an important aspect of muscle development, and the higher SCMA in newly hatched birds will result in an increase in muscle size at maturity (Mozdziak et al, 1997;Moore et al, 2005). It has been reported that early hatched nutrition increased myogenic SCMA during immediate posthatch period, and subsequently promoted BW and pectoral muscle weight during the growth phase (Mozdziak et al, 2002;Moore et al, 2005).…”
Section: Discussionmentioning
confidence: 99%